2000
DOI: 10.1046/j.1365-2958.2000.01873.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase variation of the gonococcal siderophore receptor FetA

Abstract: FetA, the recently characterized gonococcal ferric enterobactin receptor, exhibited extremely rapid phase variation between high‐ and low‐expression levels. The frequency of phase variation was ≈ 1.3% in both directions in gonococcal strain FA1090. FetA expression in the ‘high phase’ was significantly greater than the level of expression in the ‘low phase’. Expression levels correlated with the number of cytosine residues in a string of cytosines located close to the transcriptional start site for fetA between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…5A is that the frpB promoter is iron responsive in each strain tested and, furthermore, the overall amount of transcript in the complemented mutant Fko-C is significantly higher than in the other strains. However, the promoter sequence contains a tract of 11 C's between the Ϫ10 and Ϫ35 hexamers similar to the phase-variable promoter reported in the closely related N. gonorrhoeae (5). We therefore, sequenced the promoter regions in the different backgrounds and identified that indeed the length of the C tract was variable, with 10 instead of 11 C's in the Fko-C strain.…”
Section: Vol 188 2006mentioning
confidence: 68%
“…5A is that the frpB promoter is iron responsive in each strain tested and, furthermore, the overall amount of transcript in the complemented mutant Fko-C is significantly higher than in the other strains. However, the promoter sequence contains a tract of 11 C's between the Ϫ10 and Ϫ35 hexamers similar to the phase-variable promoter reported in the closely related N. gonorrhoeae (5). We therefore, sequenced the promoter regions in the different backgrounds and identified that indeed the length of the C tract was variable, with 10 instead of 11 C's in the Fko-C strain.…”
Section: Vol 188 2006mentioning
confidence: 68%
“…FetA, formerly FrpB, is an iron-repressed TonB-dependent receptor which binds ferric enterobactin. In gonococci, FetA expression can be down-regulated by phase variation (2). Inspection of the corresponding homopolymeric tracts within the meningococcal fetA promoter sequence of strain MC58 (15) suggests that phase variation is possible in this species also (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the sequence diversity of FetA, variable expression in both meningococci and gonococci (Carson et al, 2000) may also reduce the effectiveness of this protein as a vaccine component. This provides a further parallel with the PorA protein which is also phase-variable (van der Ende et al, 2000).…”
Section: Discussionmentioning
confidence: 99%